Person Re-Identification Using Deep Learning Approach: A Survey - Mallika Pandeeswari, R.; Shargunam, S.; Rajakumar, G. (Asian Journal of Engineering and Applied Technology, 2021)
Person Re-identification proof crosswise over various observation cameras with disjoint fields of view has turned out to be one of the most intriguing and testing subjects in the zone of wise video observation. Albeit a few techniques have been created, what's more, proposed, certain confinements and uncertain issues remain. In the majority of the current Re-identification proof approaches, highlight vectors are separated from sectioned still pictures or video outlines. Distinctive similitude or disparity measures have been applied to these vectors. A few strategies have utilized basic consistent measurements, while others have used models to acquire streamlined measurements. Some have made models dependent on neighborhood shading or surface data, and others have constructed models dependent on the stride of individuals. When all is said in done, the primary goal of every one of these methodologies is to accomplish a higher-exactness rate and lower computational costs.